An investigation of the use of TOEFL® Junior™ Standard scores for ESL placement decisions in secondary education. (April 2014) - Papageorgiou, Spiros; Cho, Yeonsuk
A common use of language tests is to support decisions about examinees such as placement into appropriate classes. Research on placement testing has focused on English for Academic Purposes (EAP) in higher education contexts. However, there is little research exploring the use of language tests to place students in English as a Second Language (ESL) support classes in secondary education. The present study examined the relationship between secondary school students' language test scores from a standardized English-language test and the placement of these students into ESL classes by their language teachers. Ninety-two ESL students in two English-medium schools took TOEFL ® Junior™ Standard. For the same students, data collection also included teachers' judgments regarding the ESL classes the students should attend. Strong correlations between test scores and the teacher-assigned ESL levels were found. Moreover, the results from the logistic regression analysis indicated a great degree of overlap between the teacher-assigned ESL levels and the levels predicted from the TOEFL Junior Standard scores. The findings of this study provide some preliminary evidence to support the use of TOEFL Junior Standard as an initial screening tool for ESL placement. The limitations and implications of these findings for ESL placement decisions in secondary education are also discussed.